The wedding menu - Lorini, Letizia (Gallery Books, 2025)
"One year ago, Amelie had it all. Nearly engaged to her high school sweetheart, close to her childhood best friend, and cooking at her dad's restaurant, her life was exactly what she'd ordered. Until Ian, an opinionated wedding-hater, sat beside her at a wedding and proved she might like something off-menu. Now, Amelie is unemployed, single, and taking a break from her best friend. On top of it all, she's lost all contact with Ian. When she visits his hometown to teach at a weeklong cooking conference, she hopes for a fateful meet-cute. But their reunion is explosive when Amelie discovers Ian is the son of her father's business rival. Even bigger fiasco? He only wants to be her friend. Amelie has one week to change his mind, and if the truth of why her whole life fell apart remains hidden, their love story might even end with a wedding"--